Efficacy of stereoscopic visualization and six degrees of freedom interaction in preoperative planning of total hip replacement. - Testi D; Lattanzi R; Benvegnù M; Petrone M; Zannoni C; Viceconti M; Toni A (Medical Informatics & the Internet in Medicine, 2006)
The aim of this study was to assess the accuracy of a six-degrees-of-freedom application for pre-operative planning of total hip replacement in a virtual reality (VR) environment. A test was performed estimating the system inherent accuracy. The users can move objects in the VR environment with an intrinsic accuracy almost four orders of magnitude greater than the object dimension. A second unambiguous and relevant task was defined to assess the accuracy achievable with the interface in a specific planning task. The results were compared with those obtained with 2D interfaces for both the stem and the cup component. The RMSE was assumed as an indicator of the achievable accuracy. The accuracy of the immersive interface was comparable with that achievable with a standard mouse - monitor interface. The users were consistent using the VR interface, confirming the high usability of the new interface and the steep learning curve of users unfamiliar with the new environment. This study has demonstrated that the application of VR environment for pre-operative planning of total hip replacement may help to shorten the duration of the positioning and to yield consistent results even with first-time users.